Bradykinin B1 receptor contributes to interleukin-8 production and glioblastoma migration through interaction of STAT3 and SP-1. (January 2019) - Liu, Yu-Shu; Hsu, Jhih-Wen; Lin, Hsiao-Yun; Lai, Sheng-Wei; Huang, Bor-Ren; Tsai, Cheng-Fang; Lu, Dah-Yuu
Abstract: Glioblastoma (GBM), the most aggressive brain tumor, has a poor prognosis due to the ease of migration to surrounding healthy brain tissue. Recent studies have shown that bradykinin receptors are involved in the progression of various cancers. However, the molecular mechanism and pathological role of bradykinin receptors remains unclear. We observed the expressions of two major bradykinin receptors, B1R and B2R, in two different human GBM cell lines, U87 and GBM8901. Cytokine array analysis showed that bradykinin increases the production of interleukin (IL)-8 in GBM via B1R. Higher B1R levels correlate with IL-8 expression in U87 and GBM8901. We observed increased levels of phosphorylated STAT3 and SP-1 in the nucleus as well. Using chromatin immunoprecipitation assay, we found that STAT3 and SP-1 mediate IL-8 expression, which gets abrogated by the inhibition of FAK and STAT3. We further demonstrated that IL-8 expression and cell migration are also regulated by the SP-1. In addition, expression levels of STAT3 and SP-1 positively correlate with clinicopathological grades of gliomas. Interestingly, our results found that inhibition of HDAC increases IL-8 expression. Moreover, stimulation with bradykinin caused increases in acetylated SP-1 and p300 complex formation, which are abrogated by inhibition of FAK and STAT3. Meanwhile, knockdown of SP-1 and p300 decreased the augmentation of bradykinin-induced IL-8 expression. These results indicate that bradykinin-induced IL-8 expression is dependent on B1R which causes phosphorylated STAT3 and acetylated SP-1 to translocate to the nucleus, hence resulting in GBM migration. Graphical abstract: Image 1 Highlights: Bradykinin mediates IL-8 expression and GBM migration through the B1 receptor. Bradykinin transcriptionally enhances IL-8 expression via the FAK/STAT3 and SP-1 pathways. Phosphorylated STAT3 and acetylated SP-1 modulate bradykinin-induced IL-8 expression and GBM migration.